Colonialismo no sertão pacificado: os povos do planalto de Benguela sob o Terceiro Império Português (1890-1954) - Santos, Jéssica Evelyn Pereira dos (2019)
Until the second half of the 19th century, the Angolan territory controlled by the Portuguese colonial administration was restricted to Luanda, Benguela, and Moçâmedes. Despite the contacts between native people and Europeans in the highlands, the Portuguese presence was not enough to assure the domination of the highlands by the colonial structures. The Benguela plateau’s people have maintained their political autonomies until at least the last decade of the 19th century. From this time onward, the native political autonomies were highly affected by the “pacification wars”, which have gained a bigger dimension when the Portuguese won the wars in Bié (1890) and in Bailundo (1902-1904). These military enterprises have allowed the fragile setting of the colonialism on Benguela Highlands. In this context, the role of the native authorities was transformed, limited and fragmented, but it was not completely replaced by the colonial administration. Besides that, the caravan trade’s crisis, the rubber boom, and the growth of the demand for “contract workers” have motivated conflicts for authority and leadership. Although colonial narratives tend to overlook the actions of the native subjects, these characters have assumed fundamental roles in the disputes over the power and social roles, for the development and maintenance of the colonial system as for its inquiring. The images of the native characters produced by colonial discourse are based on imperial notions of inferiority and lack of “civility”. These images are central to the process of domination of native people and their territories. The precarious conditions of native labor under colonial rule and the notion of “indigenato” are central elements to the predominance of the monolithic idea of empire as “civilizing mission”. These elements have brought direct implications to sociopolitical organizations and labor issues for native societies. Once focusing on colonial politics and practices on native peoples of Benguela Highlands, this research intends to comprehend the relationships between imperialism and social, political and cultural changes that have taken place in the region during the age of “third Portuguese empire”. This work analyses a corpus formed by colonial administrator’s reports, journals, missionary reports, ethnography material, and legislation was through the lens of “Bifurcated State” theory by Mamdani, “Invented Tradition” concept by Ranger and Hobsbawm, “colonial archive” by Mudimbe and “imperialism” by Edward Said. This work intends to contribute to the demystification of persistent images of a culturally homogeneous, tribalist, poor, dependent and illiterate sub-Saharan Africa, which have reverberated through African colonial History by erasing the native people roles in historical processes.